2004
DOI: 10.1167/iovs.03-0540
|View full text |Cite
|
Sign up to set email alerts
|

Oncofetal Fibronectin in Diabetic Retinopathy

Abstract: Use of a well-established animal model of chronic diabetic complications and cultured endothelial cells showed that diabetes-induced upregulation of oncofetal fibronectin is, in part, dependent on hyperglycemia-induced transforming growth factor-beta1 and endothelin-1. Furthermore, the data suggest that oncofetal fibronectin is involved in endothelial cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 44 publications
7
90
0
Order By: Relevance
“…We and others have previously demonstrated the upregulation of fibronectin mRNA in vascular endothelial cells exposed to high levels of glucose and in the target organs of diabetic complications, i.e. retina, kidney and heart [3,4]. We have further demonstrated that these alterations may, in part, be dependent on the hyperglycaemia-induced increase in the production of vasoactive factors such as endothelins (ETs) and subsequent activation of nuclear factor-κB (NF-κB) and activating protein-1 (AP-1) [8,9].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…We and others have previously demonstrated the upregulation of fibronectin mRNA in vascular endothelial cells exposed to high levels of glucose and in the target organs of diabetic complications, i.e. retina, kidney and heart [3,4]. We have further demonstrated that these alterations may, in part, be dependent on the hyperglycaemia-induced increase in the production of vasoactive factors such as endothelins (ETs) and subsequent activation of nuclear factor-κB (NF-κB) and activating protein-1 (AP-1) [8,9].…”
Section: Introductionmentioning
confidence: 83%
“…*p<0.05 vs control and respective LG; n=4 per treatment [28]. Increased production of ECM proteins, such as fibronectin, may be an important factor leading to the development of long-term changes such as angiogenesis in diabetic retinopathy [3,29]. Several biochemical anomalies induced by high glucose may activate Akt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies Human MVECs (Clonetics, Walkersville, MD, USA) were cultured with endothelial growth medium (Clonetics) as previously described [24]. To determine the optimal high glucose (HG) concentration, sub-confluent cells were incubated with 10, 15, 25 or 35 mmol/l D-glucose.…”
Section: Methodsmentioning
confidence: 99%
“…injection of streptozotocin (STZ; 65 mg/kg; Sigma-Aldrich) [24]. Ageand sex-matched controls were given an equal volume of citrate buffer.…”
Section: Methodsmentioning
confidence: 99%